Charting The Digital Odyssey: Exploring Challenges and Unleashing Opportunities for Journalism in The Digital Era - Sultan, Moehammad Iqbal; Amir, Andi Subhan (Ikatan Sarjana Komunikasi Indonesia, 2023)
The digital era has ushered in a transformation in journalism, reshaping news creation, dissemination, and consumption. This article examines the challenges and opportunities within contemporary journalism's digital landscape. This article comprehensively analyzes the dynamics of modern journalism in the digital age. It draws from scholarly research and industry insights to explore the evolving roles of journalists, the influence of social media, the rise of data journalism, and the imperative of media literacy. Our research combines literature reviews, industry analysis, and critical examination to provide a holistic perspective on the digital age's challenges and opportunities for journalists and media entities. The study reveals that journalists now function as information curators and investigative watchdogs in a digital information deluge. Social media is a primary news source, challenging traditional hierarchies while offering new engagement possibilities. Data journalism amplifies storytelling, but demands increased digital and statistical literacy among journalists. Promoting media literacy in society is essential for effectively navigating the digital information landscape. In conclusion, this article offers insights into contemporary journalism's challenges and prospects in the digital age. Addressing the evolving roles of journalists, the impact of social media, the rise of data journalism, and the importance of media literacy provide valuable guidance for practitioners, scholars, and media consumers. In navigating the digital frontier, journalists and media entities can maintain their pivotal roles as trusted sources of information in an ever-evolving media ecosystem.